The Mediating Effect of Language Exposure to the Student Interaction and Sociolinguistic Competence of Senior High School Students - Montalbo, Jury Rose C.; Antiporta, Mae Anne; Mangana, Chania Lnn M.; Engay Jr., Danilo G. (CV. Tripe Konsultan, 2024)
Understanding the importance of student interactions influences the process of improving sociolinguistic competence, especially since it plays a crucial role in English proficiency. This study examined whether language exposure mediates the relationship between student interactions and sociolinguistic competence among senior high school students. Data were collected from 179 respondents through adapted questionnaires assessing students' interaction, language exposure, and sociolinguistic competence. Mediation analysis using the Sobel test was conducted to test the hypothesized mediation model. Student interaction was significantly related to sociolinguistic competence, language exposure was significantly associated with sociolinguistic competence, and student interaction was significantly related to language exposure. The indirect effect of language exposure on student interaction and sociolinguistic competence significantly indicated that language exposure mediated the relationship between student interaction and sociolinguistic competence. The intervention showed the consideration of language exposure in improving students' sociolinguistic competence, especially at school. Since the study provided pieces of evidence for the mediating role of language exposure in the relationship between student interaction and sociolinguistic competence, allowing and encouraging the students to be more exposed to the language as they interact using English may be a promising avenue for enhancing sociolinguistic competence, particularly in aiming students' overall English proficiency.